The Students’ Ability in Pronouncing Centering Diphthongs of The Beginner Level Students of English Genius Course Simpang Okus - Novarita Novarita (International Journal of Language Teaching and Education, 2017)
The problem of this study was concerned to the students’ ability in Pronouncing Centering Diphthongs of The Beginner Level Students of English Genius Course Simpang OKUS. The objective of this study were to find out the students’ ability ability in Pronouncing Centering Diphthongs of The Beginner Level Students of English Genius Course Simpang OKUS and to find out the factors influence the students’ ability in Pronouncing Centering Diphthongs of The Beginner Level Students of English Genius Course Simpang OKUS. In this investigation, the writer used descriptive method. The population of the research was the beginner level students of English Genius Course Simpang OKUS. The were 73 students, which was consisted of four classes. In this research, the researcher used all the population, the total population was 73 students as the sample. The students’ ability in Pronouncing Centering Diphthongs of The Beginner Level Students of English Genius Course Simpang OKUS was good or relatively able. Based on the result of questionnaire, the dominant factors that influence the students’ ability in Pronouncing Centering Diphthongs of The Beginner Level Students of English Genius Course Simpang OKUS were outcomes and engagement. Keywords : Ability, Pronouncing, Centering Diphthong